2019
DOI: 10.1007/s10995-019-02778-5
|View full text |Cite
|
Sign up to set email alerts
|

Exploring Multiple Dimensions of Young Women’s Fertility Preferences in Malawi

Abstract: Introduction-Standard survey measures of fertility preferences, such as the desire for and preferred timing of future births, do not capture the complexity of individuals' preferences. New research focuses on additional dimensions of emotions and expectations surrounding childbearing. Few quantitative studies, however, consider the influence of all three dimensions of fertility preferences concurrently. Methods-Using longitudinal survey data from the Tsogolo la Thanzi project (2009-2012) in Malawi, this study … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…Building on previous evidence from SSA on important predictors of fertility behaviours, access to reproductive health care, and social pressure to conceive ( Barden-O’Fallon, 2005a ; Fledderjohann, 2017 ; Gerrits, 2012 ; Gibby & Luke, 2019 ; Grant, 2015 ; Grant & Furstenberg, 2007 ; Rouchou, 2013 ; Smith-Greenaway, 2016 ; Sundby, 2002 ), the key sociodemographic characteristics examined in this study include age in years, number of years of schooling completed, household wealth, total number of living children, and belief that children just happen. Due to the small sample sizes limiting statistical power, variables were coded as continuous for age, education, and parity.…”
Section: Methodsmentioning
confidence: 99%
“…Building on previous evidence from SSA on important predictors of fertility behaviours, access to reproductive health care, and social pressure to conceive ( Barden-O’Fallon, 2005a ; Fledderjohann, 2017 ; Gerrits, 2012 ; Gibby & Luke, 2019 ; Grant, 2015 ; Grant & Furstenberg, 2007 ; Rouchou, 2013 ; Smith-Greenaway, 2016 ; Sundby, 2002 ), the key sociodemographic characteristics examined in this study include age in years, number of years of schooling completed, household wealth, total number of living children, and belief that children just happen. Due to the small sample sizes limiting statistical power, variables were coded as continuous for age, education, and parity.…”
Section: Methodsmentioning
confidence: 99%
“…Should a divorce occur, one's fertility regains importance to solidify a new relationship (Reniers 2003). Even within a single partnership, pregnancy intentions and desired family size can change frequently (Yeatman and Sennott 2015;Yeatman, Sennott, and Culpepper 2013;Gibby and Luke 2019).…”
Section: Contextmentioning
confidence: 99%
“…A series of recent studies specifically assessed the predictive validity of fertility desires in sub-Saharan Africa. Many found that women who report wanting more children are more likely to have additional children than are women who report a desire to stop childbearing (Gibby and Luke 2019;Hayford and Agadjanian 2012;Kodzi et al 2010;Machiyama et al 2015Machiyama et al , 2019Speizer and Lance 2015). Yet a 2019 systematic review of timing desires found inconsistent results.…”
Section: Introductionmentioning
confidence: 99%